1979
DOI: 10.1126/science.205.4411.1089
|View full text |Cite
|
Sign up to set email alerts
|

The Colorado Plateaus: Cultural Dynamics and Paleoenvironment

Abstract: Convergent archeological, geological, palynological, dendrochronological, and radiometric data provide a paleoenvironmental record for the American Southwest at a level of detail and time resolution not previously achieved. Many prehistoric cultural and demographic changes on the Colorado Plateaus coincided with environmental fluctuations defined by precisely dated geoclimatic and bioclimatic indicators. These coincidences support the interpretation that socioeconomic changes and population displacements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 41 publications
4
75
1
Order By: Relevance
“…Approximately 30 years ago Euler et al (1979), using a variety of available climate-proxy records, showed that environmental change in the southern Colorado Plateau was accompanied by cultural and demographic responses during the past 2,300 years. One of the measures of cultural change they invoked was the distribution of tree-ring cutting dates over time, and one of the measures of climate change they employed was normalized tree-ring widths (principally a measure of annual precipitation).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30 years ago Euler et al (1979), using a variety of available climate-proxy records, showed that environmental change in the southern Colorado Plateau was accompanied by cultural and demographic responses during the past 2,300 years. One of the measures of cultural change they invoked was the distribution of tree-ring cutting dates over time, and one of the measures of climate change they employed was normalized tree-ring widths (principally a measure of annual precipitation).…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of erosion is thought to be a result of either livestock overgrazing or short-term climatic change. Previous work on the causes of increased gullying is summarized by Euler et al (1979). Along the Rio Puerco, east of Grants, New Mexico, gullying apparently began in the 1840s.…”
Section: D-30mentioning
confidence: 99%
“…2) Irrigation is not a likely response to a period of environmental deterioration and crop failures. Instead, the adoption of irrigation would probably have occurred during periods of relative environmental stability, when food was available to support the initial construction and subsequent rebuilding of dams and canals, Significantly, recent palynological and dendrochronological evidence suggests that climatic conditions around A.D. 1000 and 1100 were not deteriorating, but were wet and favorable for agriculture (see Euler et al 1979). 3) In the Little Colorado region it would be extremely difficult for a simple egalitarian society to develop and maintain irrigation systems, 4) Prehistoric subsistence, settlement and organizational change were not neces sarily caused by an environmental shift, but could have resulted from a feedback cycle between sociopolitical development, subsistence intensification and in creased regional exchange.…”
Section: I I Imentioning
confidence: 99%